Christian Education for a Generation of Amusement - SIBA, Balázs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2018)
The expectations of the children of our “amusement society” are different to what they used to be a generation or two ago. I highlight a few aspects, which might be relevant (albeit not new) to how we address contemporary young people. I would like to raise awareness of aspects which are still indispensable and which have probably gained importance for the process of Christian Education, not because they are novel, but because they are fundamental. What has not changed, is the need for real human relationships, the importance of personal involvement, and the delight of performing meaningful tasks. At Christain Education, pupils not only learn about something, but they are also invited into the in-between space of a dialogue with God. This involves learning by doing, experimenting with practices, which are in line with our spiritual heritage, and which offer our pupils a chance to engage in dialogue with God (prayer, meditation, silence, fasting, journaling, singing etc.).